Law Enforcement Policies and Procedures Evaluation in Accordance with the Americans with Disabilities Act as it Applies to Individuals Who are Deaf or Hard of Hearing - Powell, Erin Rachel (My University, 2015)
Approximately nine percent of the United States (U.S.) population is deaf and/or hard of hearing. This population entails distinct communities, hard of hearing, deaf, and Deaf, each requiring separate distinct services. Law enforcement agencies are to incorporate policies to ensure that equal access is being given to those individuals who are deaf and/or hard of hearing, as they are protected under the American’s with Disabilities Act. The Monell decision set a precedent for law enforcement agencies to implement policies in order to avoid § 1983 lawsuits. Officers must be trained to ensure that policies are effectively implemented to achieve effective communication. Law enforcement agencies must provide communication aids and services free of charge requested by the individual, based on their mode of communication. Through a convenience sample of 68 existing law enforcement policies, the study was conducted to evaluate those policies as well as provide policy recommendations. Identifying deficiencies in the existing policies can assist law enforcement administration in establishing a risk management plan. The U.S. Department of Justice (DOJ) provides sufficient resources in assisting law enforcement agencies in achieving effective communication with individuals who are deaf and/or hard of hearing.
TABLE OF CONTENTS | I. INTRODUCTION - 1 | Purpose - 1 | Rationale - 4 | II. LITERATURE REVIEW - 9 | Americans with Disabilities Act - 9 | Bureaucratic Theory - 11 | Monell v. Department of Social Services of the City of New York (1978) - 14 | Law Enforcement Encounters With Individuals Who Are Deaf or Hard of Hearing - 16 | Court Cases - 19 | Involvement of United States Department of Justice - 2 | Lodi Police Department - 23 | Minneapolis Police Department - 24 | Emergency Management Responders - 27 | Summary - 28 | III. METHODOLOGY - 30 | Sampling Rationale and Procedure - 30 | IV. RESULTS - 36 | Distribution by Types - 37 | Population - 38 | Components - 41 | V. DISCUSSION - 50 |
Keywords: Policy; Americans with Disabilities Act; Deaf or Hard of Hearing; Law Enforcement